Cyclic behaviour of beam-column joints made of crumb rubberised concrete (CRC) and traditional concrete (TC). (June 2022) - Chu, Liusheng; Wang, Shuaiqi; Li, Danda; Zhao, Jun; Ma, Xing
Abstract: Crumb rubberised concrete (CRC) is a sustainable material that recycles rubber particles from end-of-life tyres as partial fine aggregates in concrete. To promote the applications of CRC in building structures, this paper presents an experimental study on the cyclic behaviour of beam-column joints from both CRC and traditional concrete (TC) frame structures. CRC with 15% rubber content by sand volume was employed. Three full scale CRC joint samples and one full scale TC sample were tested. Varying axial loads were applied on the top of columns and anti-symmetrical low-frequency cyclic loads were applied at the two beam ends. The failure modes, hysteretic behaviour, stiffness degradation, bearing capacity degradation, shearing capacity, displacement ductility and strain response of CRC and TC joints were investigated and compared. Both CRC and TC joint samples reached their ultimate loads due to shear failure. When CRC and TC were with similar strengths, the first crack loads, yielding loads, ultimate loads and ultimate displacements for TC and CRC joints at the same axial compression ratios were comparable with slight differences within 5%. However, CRC joints exhibited an improved energy dissipation ability by up to 10.4% over TC samples.